2018
DOI: 10.1063/1.5054929
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic electron heating in the laser and quasi-static electric and magnetic fields

Abstract: The dynamics of relativistic electrons in the intense laser radiation and quasi-static electromagnetic fields both along and across to the laser propagating direction are studied in the 3/2 dimensional Hamiltonian framework. It is shown that the unperturbed oscillations of the relativistic electron in these electric fields could exhibit a long tail of harmonics which makes an onset of stochastic electron motion be a primary candidate for electron heating. The Poincaré mappings describing the electron motions i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…Noticing that the Hamiltonian in Eq. ( 5) has similar structure to that for electron in the laser and quasi-static electric fields considered in [16], we find that, for relativistic case a > 1, unperturbed (or weakly perturbed) electron trajectories have characteristics of zigzag time dependence of canonical coordinate χ (e.g., see the upper panel of Fig. 1).…”
supporting
confidence: 63%
“…Noticing that the Hamiltonian in Eq. ( 5) has similar structure to that for electron in the laser and quasi-static electric fields considered in [16], we find that, for relativistic case a > 1, unperturbed (or weakly perturbed) electron trajectories have characteristics of zigzag time dependence of canonical coordinate χ (e.g., see the upper panel of Fig. 1).…”
supporting
confidence: 63%
“…However, from Eq. (3) we have zz P C U(y) ( 1)P         , which indicates that whereas static electric field could enhance the electron-laser interaction when U approaches C  , the superluminal phase velocity of laser radiation, 1  , would reduce it [19]. For simplicity, in the rest of this paper, we consider the luminal case, 1  , and assume that x P0  .…”
Section: /2d Hamiltonian and Electron Trajectoriesmentioning
confidence: 99%
“…where j  is the "time" of previous "collision". In [19] it was shown that the transverse electric filed itself leads to stochastic electron heating, depending on laser polarization, up to the energies…”
Section: High-n Resonances and Stochastic Electron Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that, by employing the integrals of motion for electrons in laser and quasi-static electromagnetic fields, the electron dynamics can be described by the 3/2 dimensional (3/2D) Hamiltonian approach [25,26], which has greatly simplified the analysis of electron dynamics [27,28] and the boundary of electron energy due to the stochastic motion was obtained by finding the Chirikov-like mapping [29]. Such method has been extended to the case of electrons in the colliding laser waves [30] by employing proper canonical variables and effective time, such that the new Hamiltonian becomes time independent when the perturbative laser wave is absent, where the electron dynamics for luminal planar laser waves, which are linearly polarized in the same direction, and transverse canonical momentum be-ing zero was exhaustively examined.…”
Section: Introductionmentioning
confidence: 99%